Mapping the design and implementation of seed sector regulation: The case of Uganda - Kuhlmann, Katrin; Nalinya, Adron Naggayi; Francis, Tara; Spielman, David J. (International Food Policy Research Institute, 2023)
An enabling environment with clear, inclusive, and transparent seed laws, policies, regulations, and guidelines is the foundation for an efficient and effective seed sector. If well designed and implemented, the legal and regulatory framework can facilitate market diversification, supervision and quality control of seed and other forms of planting material, promotion of private sector participation, farmer access to improved seed varieties, reduced barriers for the movement of seeds across borders, and food security. This study uses Regulatory Systems Maps (RSMs), a mapping tool for legal and regulatory processes and procedures, as a primary comparative method to assess the progress and dynamics in Uganda’s seed system along four key dimensions of the seed systems regulatory value chain: (i) early generation seed (EGS) production and distribution, (ii) varietal registration and release processes, (iii) seed quality assurance systems, and (iv) seed trade. The RSMs document and illustrate the processes and procedures contained in Uganda’s seed legal and regulatory systems, analytically isolating intervention points, proposed legal and regulatory changes, good practices and legal innovations, and systemic shifts over time, while also integrating important dimensions such as gender, inclusion, and flexibility that can address farmers’ needs, reduce costs, and increase participation in seed systems. The data and information used to compile the Uganda RSMs were developed and validated through a series of consultations with an array of stakeholders spanning both the public and private sectors. The findings of the RSMs showed that, despite the comprehensive nature of Uganda’s seed rules and regulations and some notable innovations, implementation is a persistent challenge, and regulatory gaps and inconsistencies continue to exist. The RSMs indicate the need to take various measures to improve the enabling environment for seed trade in Uganda, including reviewing the current seed law, which is largely outdated; updating the existing seed regulations; adopting plant variety protection (PVP) regulations to implement the PVP Act; developing guidelines on agricultural research; and building capacity in both the public and private sectors.